Impact of ownership structure on dividend payout in Pakistani non-financial sector - Muzammal Ilyas Sindhu; Shujahat Haider Hashmi; Ehtasham Ul Haq (Cogent Business & Management, 2016)
The purpose of this study is to analyze the impact of ownership structure on dividend payout (DIV) ratio of 100 companies related to non-financial sector listed in Karachi stock exchange for the sample period of 2011–2015. Fixed effects model as a panel data analysis technique indicates that managerial ownership (MO) has shown significant and negative impact on DIV which indicates that as MO rise, they will prefer to retain instead of distribution. Institutional ownership is showing significant and positive behavior with DIV ratio which also showing favorable arguments for dividend distribution. Change in earnings and operating cash flows as control variables are not making variation in DIV. Further, firms having favorable firm's value and higher firm's size lead to distribute more dividends with good faith and reputation. Leverage and DIV ratio relationship are an indication of cash flow theory, all earnings must be distributed among shareholders while positive and favorable NPV projects must be availed through debt financing. This study provides supports to shareholders in adjusting their investment strategies because it provides information regarding dividend policies.
Keywords: 650